Zapisz w najprostszej postaci a] 2[x+3]+4[4-3x] b ]3[x-6]+4[x-6] c]2k[k-3]+4k[k+4] d] 7[3xdo kwadratu +5x]-5x[3-6x] e] 3[x-6]-5[x-6] f] 2[x+3]-3[4-3x] g] 2k[k-3]-4k[k+4]



Odpowiedź :

a) 2(x+3)+4(4-3x)= 2x+6+16-12x= -10x+24 = -5x+12

b) 3(x-6)+4(x-6)= 3x-18+4x-24= 7x-42 = x-6

c) 2k(k-3)+4k(k+4)= 2[tex]k^{2}[/tex]-6k+4[tex]k^{2}[/tex]+16k= 6[tex]k^{2}[/tex]+10k= 3[tex]k^{2}[/tex]+5k= k(3k+5)

d) 7(3[tex]x^{2}[/tex]+5x)-5x(3-6x)= 21[tex]x^{2}[/tex]+35x-15x+30[tex]x^{2}[/tex]= 51[tex]x^{2}[/tex]+20x= x(51x+20)

e) 3(x-6)-5(x-6)= 3x-18-5x+30= -2x+12 = -x+6

f) 2(x+3)-3(4-3x)= 2x+6-12+9x= 11x-6

g) 2k(k-3)-4k(k+4)= 2[tex]k^{2}[/tex]-6k-4[tex]k^{2}[/tex]-16k= -2[tex]k^{2}[/tex]-22k= -[tex]k^{2}[/tex]-11k= k(-k-11)